Paternal transmission of congenital myotonic dystrophy. - Bergoffen, J (1994)
The congenital form of myotonic dystrophy is reported to be almost exclusively, if not exclusively, maternally transmitted. We present a case of congenital myotonic dystrophy which was inherited from a mildly affected father. This family illustrates that the congenital form of myotonic dystrophy can occur without intrauterine or other maternal factors related to the disease. The possibility of paternal transmission of the congenital form of myotonic dystrophy could be considered when counselling myotonic dystrophy patients and their families.